Jammu and Kashmir Government Draft 7th Five Year Plan 1985-90 and Annual Plan 1985-86 Vol. VII Transport and Communication - Government of Jammu and Kashmir (Government of Jammu and Kasmir, 1984)
The Draft 7th Five-Year Plan (1985–90) for Jammu and Kashmir outlines a comprehensive strategy for developing transport, communication, and horticultural infrastructure across the state. Due to the region’s challenging hilly terrain and limited railway access, the plan emphasizes road construction and maintenance, targeting the connection of isolated rural villages and supporting socio-economic sectors such as agriculture, tourism, and industry. With projected funding of Rs. 12,000 million for new road constructions and additional allocations for urban road upgrades, the plan addresses bottlenecks, bridges, and strategic highways including the Mughal Road to enhance regional connectivity. Urban transport improvements and the modernization of state motor garages, including vehicle acquisitions and staffing expansion, aim to handle growing traffic and operational demands. Simultaneously, the plan details initiatives for the Gardens, Parks, and Floriculture Department, allocating ₹486.00 lacs to enhance horticultural infrastructure, establish production and marketing divisions, develop children’s parks, and implement maintenance and renovation projects. Emphasis is placed on employment generation, sustainable management, and tourism promotion through parks and garden enhancements. Overall, the plan envisions integrated infrastructure development, improved mobility, and socio-economic growth, balancing urbanization pressures, environmental considerations, and long-term sustainability.
Planning and Development Department, Jammu November 1984
Planning and Development Department, Jammu November 1984
Keywords: Jammu And Kashmir; Transport Infrastructure; Road Development; Urban Transport; Motor Garages; Tourism Connectivity; Budget Allocation; Horticulture; Parks And Gardens; Employment Generation; Irrigation Systems; Socio-Economic Development